Alkali-free glass substrate, laminated substrate, and method for producing glass substrate
By preparing alkali-free glass substrates with specific composition and heat treatment conditions, the residual strain problem caused by the difference in thermal expansion coefficients in the heat treatment process of silicon substrates and glass substrates is solved, and the grinding rate and processability of glass substrates are improved. It is suitable for semiconductor manufacturing processes .
Patent Information
- Application Number
- CN202411342598.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2016-08-05
- Filing Date
- 2017-05-22
- Publication Date
- 2025-01-07
AI Technical Summary
The prior art In the heat treatment process of silicon substrates and glass substrates, residual strain occurs due to differences in thermal expansion coefficients, and it is difficult to obtain a glass substrate with small plate thickness deviation and high flatness.
A specific alkali-free glass substrate is used, which contains more than 11.0% of Al2O3, more than 8.0% of B2O3, and more than 1% of SrO, and the average thermal expansion coefficient at 100°C to 200°C is 3.10ppm/℃ to 3.70ppm/℃/ A glass substrate with a Young's modulus of less than 76.0 GPa and a density of more than 2.42 g/cm3 was prepared by melting, clarification, forming and slow cooling processes to meet the specific cooling speed conditions to match the thermal expansion coefficient of the silicon substrate.
It is realized that the residual strain is reduced when the silicon substrate and the glass substrate are bonded, and the grinding rate and processability of the glass substrate are improved. It is suitable for supporting substrates and cover glass in semiconductor manufacturing processes.
Smart Images

Figure CN119263631A_ABST
Abstract
Description
[0001] The present application is a divisional application of the invention application with application number 201780031202.4, application date May 22, 2017, and invention name “Method for manufacturing alkali-free glass substrate, laminated substrate and glass substrate”. Technical Field
[0002] The present invention relates to an alkali-free glass substrate, a laminated substrate and a method for manufacturing a glass substrate. Background Art
[0003] Image sensors such as chip scale packages (CSP) are known to have a glass substrate attached to a silicon substrate for protection. For example, Patent Document 1 discloses a glass for a silicon base having an elongation due to thermal expansion close to that of a silicon substrate bonded to the glass.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent No. 3153710 Summary of the invention
[0007] In the semiconductor assembly process, the silicon substrate and the glass substrate are cut separately in the wafer state, and then the silicon substrate and the glass substrate are bonded together to perform a series of assembly processes such as chip bonding, wire bonding, and molding. In recent years, assembly by wafer-level packaging technology has also been proposed, which is a process of bonding the silicon substrate and the glass substrate in the wafer state and then cutting them.
[0008] In order to bond a silicon substrate to a glass substrate, a glass substrate with small thickness deviation (TTV) and high flatness is required. However, it is difficult to obtain the desired thickness deviation and flatness with current glass molding technology, so it is necessary to grind the molded glass substrate to improve the thickness deviation and flatness.
[0009] The glass substrate used in the image sensor is processed by processing the outer shape of the blank plate manufactured by the float process into a wafer state, and then the outer dimensions of the wafer are adjusted to the standard by a grinding process (lapping) to remove the strain on the surface of the wafer and a polishing process (polishing) to remove micro cracks on the surface of the wafer and reduce the surface roughness. In order to obtain a glass substrate with small thickness deviation and high flatness with good productivity, a high grinding rate (grinding rate) in the grinding process is required.
[0010] In addition, a heat treatment process is required to bond the silicon substrate and the glass substrate. In the heat treatment process, for example, the laminated substrate formed by bonding the silicon substrate and the glass substrate at a temperature of 200°C to 400°C is cooled to room temperature. At this time, if there is a difference in the thermal expansion coefficient between the silicon substrate and the glass substrate, the difference in thermal expansion will cause a large residual strain (residual deformation) in the silicon substrate.
[0011] Furthermore, in the wafer-level packaging technology, since a silicon substrate and a glass substrate are bonded together in a wafer state, residual strain is likely to occur in the silicon substrate even if there is a difference in thermal expansion coefficient, which has not been a problem in the past.
[0012] Patent Document 1 proposes a glass for silicon substrates, characterized in that the ratio α1 / α2 of the elongation α1 of the glass based on thermal expansion to the elongation α2 of the silicon substrate bonded to the glass based on thermal expansion is in the range of 0.8 to 1.2. However, in the glass of the embodiment disclosed in Patent Document 1, the thermal expansion coefficient is not sufficiently consistent with the silicon substrate, and residual strain is easily generated in the silicon substrate in the wafer-level packaging technology.
[0013] Therefore, the present invention provides a glass substrate and a method for manufacturing a glass substrate having a high grinding rate and a small residual strain generated in the silicon substrate during the heat treatment process of bonding the silicon substrate and the glass substrate. In addition, the present invention provides a laminated substrate using the glass substrate. In addition, the present invention provides a glass substrate, a laminated substrate, or a method for manufacturing a glass substrate, wherein the glass substrate is a glass substrate for at least one of a supporting substrate and a cover glass for a semiconductor manufacturing process, and has a high grinding rate and excellent processability.
[0014] The present inventors have found that a glass substrate having a high grinding rate and a thermal expansion coefficient matching that of a silicon substrate can be obtained by controlling the glass composition and properties such as the thermal expansion coefficient, Young's modulus and density to fall within specific ranges, thereby completing the present invention.
[0015] The glass substrate of the present invention is characterized in that it is an alkali-free glass substrate, contains 11.0% or more of Al2O3, 8.0% or more of B2O3, and 1% or more of SrO in terms of molar percentage based on oxides, and has an average thermal expansion coefficient α at 100°C to 200°C. 100 / 200 The temperature is 3.10ppm / ℃~3.70ppm / ℃, the Young's modulus is below 76.0GPa, and the density is 2.42g / cm 3 above.
[0016] The glass substrate of the present invention has a degree of abrasion of 55 or more and is an alkali-free glass substrate used for at least one of a supporting substrate and a cover glass for a semiconductor manufacturing process.
[0017] The laminated substrate of the present invention is characterized by being formed by laminating the alkali-free glass substrate and the silicon substrate.
[0018] The method for manufacturing an alkali-free glass substrate of the present invention is characterized by comprising the following steps:
[0019] The melting step is to heat the glass raw materials to obtain molten glass.
[0020] a clarification step to remove bubbles from the molten glass,
[0021] a forming step of forming the molten glass into a plate-shaped glass ribbon, and
[0022] A slow cooling step, slowly cooling the glass ribbon to room temperature;
[0023] The composition of the obtained glass substrate contains 11.0% or more of Al2O3, 8.0% or more of B2O3, and 1% or more of SrO in terms of molar percentage based on oxides.
[0024] The composition of the obtained glass substrate and the viscosity of the glass ribbon in the slow cooling step are 10 13 When the temperature of d·Pa·s reaches 10 14.5 The average cooling rate R (unit: °C / min) of the temperature in d·Pa·s satisfies the following conditions (1) to (3).
[0025] Condition (1): 0.0181×(SiO2 content)+0.0004×(Al2O3 content)+0.0387×(B2O3 content)+0.0913×(MgO content)+0.1621×(CaO content)+0.1900×(SrO content)+0.2180×(BaO content)+0.0424×(ZnO content)+0.0391×log 10 R is 3.10~3.70
[0026] Condition (2): 0.0218×(SiO2 content)+0.0302×(Al2O3 content)+0.0181×(B2O3 content)+0.0330×(MgO content)+0.0351×(CaO content)+0.0488×(SrO content)+0.0634×(BaO content)+0.0419×(ZnO content) is 2.42 or more
[0027] Condition (3): 0.677×(content of SiO2)+1.598×(content of Al2O3)-0.220×(content of B2O3)+1.466×(content of MgO)+1.135×(content of CaO)+0.667×(content of SrO)+0.298×(content of BaO)+1.027×(content of ZnO) is 76.0 or less [In conditions (1) to (3), the contents of SiO2, Al2O3, B2O3, MgO, CaO, SrO, BaO and ZnO are expressed in terms of molar percentage based on the oxides contained in the obtained glass.]
[0028] The present invention can provide a glass substrate, a laminated substrate or a method for manufacturing a glass substrate having a high grinding rate, excellent processability and a thermal expansion coefficient matching that of a silicon substrate. In addition, the present invention can provide a glass substrate, a laminated substrate or a method for manufacturing a glass substrate, wherein the glass substrate is a glass substrate for at least one of a supporting substrate and a cover glass for a semiconductor manufacturing process, has a high grinding rate and excellent processability. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 (A) and Figure 1 (B) shows a glass substrate according to one embodiment of the present invention bonded to a silicon substrate, Figure 1 (A) is a cross-sectional view before bonding. Figure 1 (B) is a cross-sectional view after bonding.
[0030] Figure 2 The value obtained by equation (1) and α 100 / 200 A graph showing the error in the value of .
[0031] Figure 3 A graph showing a value obtained by equation (2) and a density error is shown.
[0032] Figure 4 The graph shows a graph of the value obtained by the formula (3) and the error in the Young's modulus.
[0033] Figure 5 The value obtained by equation (4) and α 200 / 300 / α 50 / 100 A graph showing the error in the value of .
[0034] Figure 6 It means that the value obtained by equation (5) and α 200 / 300 -α 50 / 100 A graph showing the error in the value of . DETAILED DESCRIPTION
[0035] Hereinafter, one embodiment of the present invention will be described.
[0036] In addition, in this specification, unless otherwise specified, the content of each component in the glass substrate and the manufacturing method thereof is expressed as a molar percentage based on the oxide.
[0037] In addition, in this specification, unless otherwise specified, "to" indicating a numerical range is used to mean that the numerical values described before and after it are included as the lower limit and the upper limit.
[0038] Figure 1 (A) and Figure 1 (B) shows a glass substrate according to one embodiment of the present invention bonded to a silicon substrate. Figure 1 The glass substrate G1 obtained by the present invention shown in (A) and the silicon substrate 10 are bonded together at a temperature of, for example, 200° C. to 400° C. with the resin 20 sandwiched therebetween. Figure 1 (B) shows a laminated substrate 30. As the silicon substrate 10, for example, a wafer (for example, a wafer containing silicon as a component, such as a silicon wafer) can be used. The resin 20 can be any resin as long as it can withstand a temperature of 200°C to 400°C.
[0039] The glass substrate of the present invention is an alkali-free glass substrate. The alkali-free glass substrate preferably has an alkali metal oxide content of 0% to 0.1%. The alkali metal oxide content is more preferably 0.05% or less, further preferably 0.02% or less, and particularly preferably substantially free of alkali metal oxides. If the alkali metal oxide content is 0.1% or less, alkali ions are difficult to diffuse into the silicon substrate during the heat treatment step of bonding the silicon substrate and the glass substrate.
[0040] Here, substantially containing no alkali metal oxide means that no alkali metal oxide is contained at all or the alkali metal oxide may be contained in the form of impurities inevitably mixed in during production. Examples of the alkali metal oxide include Li2O, Na2O, and K2O.
[0041] The glass substrate of the present invention contains 11.0% or more of Al2O3, 8.0% or more of B2O3, and 1% or more of SrO in terms of molar percentage based on oxides. The glass substrate of the present invention preferably has the following composition.
[0042] SiO2: 50% to 75%, Al2O3: 11.0% to 16%, B2O3: 8.0% to 16%, MgO: 0% to 10%, CaO: 0% to 10%, SrO: 1% to 10%, BaO: 0% to 10%, ZnO: 0% to 10%
[0043] SiO2 is a component that forms the skeleton of glass. The content of SiO2 is preferably 50% or more, more preferably 55% or more, further preferably 58% or more, and particularly preferably 60% or more. If the content of SiO2 is 50% or more, heat resistance, chemical durability and weather resistance become good. In addition, the content of SiO2 is preferably 75% or less, more preferably 72% or less, further preferably 70% or less, and particularly preferably 66% or less. If the content of SiO2 is 75% or less, the viscosity of the glass will not become too high when it is melted, the meltability becomes good, and the density becomes large.
[0044] The content of Al2O3 is 11.0% or more, preferably 11.5% or more, and more preferably 12% or more. If the content of Al2O3 is 11.0% or more, the difference in thermal expansion coefficient with the silicon substrate becomes smaller, and the weather resistance, heat resistance and chemical durability become good. In addition, the content of Al2O3 is preferably 16% or less, more preferably 15% or less, further preferably 14% or less, and particularly preferably 13% or less. If the content of Al2O3 is 16% or less, the viscosity of the glass will not become too high when it is melted, the meltability becomes good, it becomes difficult to devitrify, and the Young's modulus can be reduced.
[0045] The content of B2O3 is preferably 7.5% or more, more preferably 8.0% or more, and further preferably 9% or more. If the content of B2O3 is 7.5% or more, preferably 8.0% or more, the viscosity of the glass will not become too high when it is melted, the meltability will be good, it will be difficult to lose clarity, and the grindability can be guaranteed. In addition, the content of B2O3 is preferably 16% or less, more preferably 14% or less, further preferably 13% or less, and particularly preferably 12% or less. If the content of B2O3 is 16% or less, the glass transition temperature can be increased and the density can be increased.
[0046] MgO is not an essential component, but by including it, the difference in thermal expansion coefficient with the silicon substrate becomes smaller, the viscosity of the glass when it is melted does not become too high, the meltability becomes good, and the weather resistance is improved. When MgO is included, the content of MgO is preferably 1% or more, and more preferably 2% or more. In addition, the content of MgO is preferably 10% or less, more preferably 9% or less, further preferably 8% or less, and particularly preferably 7% or less. If the content of MgO is 10% or less, it becomes difficult to devitrify, and the Young's modulus can be reduced.
[0047] CaO is not an essential component, but by containing it, the viscosity of the glass will not become too high when it is melted, the meltability will become good, and the weather resistance will be improved. When CaO is contained, the content of CaO is preferably 0.5% or more, and more preferably 1% or more. In addition, the content of CaO is preferably 10% or less, more preferably 9% or less, further preferably 8% or less, and particularly preferably 7% or less. If the content of CaO is 10% or less, it becomes difficult to devitrify, and the Young's modulus can be reduced.
[0048] The content of SrO is 1% or more, preferably 1.5% or more, more preferably 3% or more, and further preferably 4% or more. By making the content of SrO 1% or more, the viscosity of the glass during melting will not become too high, the melting property will become good, the weather resistance will be improved, and the density can be increased. In addition, the content of SrO is preferably 10% or less, more preferably 9% or less, and further preferably 8% or less. If the content of SrO is 10% or less, it becomes difficult to devitrify.
[0049] BaO is not an essential component, but by containing it, the viscosity of the glass during melting will not become too high, the melting property will become good, the weather resistance will be improved, and the density can be increased. When BaO is contained, the content of BaO is preferably 0.5% or more, more preferably 1% or more. The content of BaO is preferably 10% or less, more preferably 9% or less, further preferably 8% or less, and particularly preferably 7% or less. If the content of BaO is 10% or less, it becomes difficult to devitrify.
[0050] ZnO is not an essential component, but by containing it, the solubility can be improved and the thermal expansion coefficient can be adjusted. When ZnO is contained, the content of ZnO is preferably 0.5% or more, more preferably 1% or more. The content of ZnO is preferably 10% or less, more preferably 9% or less, further preferably 8% or less, and particularly preferably 7% or less. By making the content of ZnO 10% or less, the devitrification temperature of the glass can be lowered.
[0051] For the glass substrate of the present invention, the total content of MgO and CaO is preferably 1% or more, more preferably 2% or more, and further preferably 3% or more. If the total content of MgO and CaO is 1% or more, it is easy to match the thermal expansion coefficient of the glass substrate with that of the silicon substrate. In addition, the total content of MgO and CaO is preferably 15% or less, more preferably 13% or less, and further preferably 10% or less. If the total content of MgO and CaO is 15% or less, it is possible to reduce the Young's modulus and increase the density.
[0052] For the glass substrate of the present invention, the total content of MgO, CaO, SrO, BaO and ZnO is preferably 7% or more, more preferably 9% or more, and further preferably 10% or more. When the total content of MgO, CaO, SrO, BaO and ZnO is 7% or more, it is easy to match the average thermal expansion coefficient of the glass substrate with that of the silicon substrate, and the density can be increased.
[0053] When the glass substrate of the present invention is used as a cover glass of an image sensor, it is preferably a glass substrate that does not easily absorb visible light. For this purpose, the content of Fe2O3 is preferably 200 ppm or less, more preferably 150 ppm or less, further preferably 100 ppm or less, and particularly preferably 50 ppm or less, based on the mass parts per million of the oxide.
[0054] In order to improve thermal conductivity and make the meltability good, the glass substrate of the present invention preferably contains Fe2O3 of more than 200ppm and less than 1000ppm in terms of mass parts per million based on oxide. If the content of Fe2O3 exceeds 200ppm, the thermal conductivity of the glass substrate can be improved and the meltability is good. If the content of Fe2O3 is less than 1000ppm, the absorption of visible light will not become too strong. The content of Fe2O3 is more preferably more than 300ppm, further preferably more than 400ppm, and particularly preferably more than 500ppm. The content of Fe2O3 is more preferably less than 800ppm, further preferably less than 700ppm, and particularly preferably less than 600ppm.
[0055] The glass substrate of the present invention may contain, for example, SnO 2 , SO 3 , Cl, F, and the like as a clarifier.
[0056] In order to improve weather resistance, solubility, devitrification, ultraviolet shielding, infrared shielding, ultraviolet transmittance or infrared transmittance, etc., the glass substrate of the present invention may contain, for example, Li2O, WO3, Nb2O5, V2O5, Bi2O3, MoO3, P2O5, Ga2O3, I2O5, In2O5 and Ge2O5.
[0057] In order to improve the chemical durability of glass, the glass substrate of the present invention may contain ZrO2, Y2O3, La2O3, TiO2 and SnO2 in the glass in a total amount of preferably 2% or less, more preferably 1% or less, and further preferably 0.5% or less.
[0058] In consideration of environmental load, the glass substrate of the present invention preferably contains substantially no As 2 O 3 and Sb 2 O 3 .
[0059] The average thermal expansion coefficient α of the glass substrate of the present invention at 100°C to 200°C 100 / 200It is 3.10 ppm / °C or more, preferably 3.20 ppm / °C or more, more preferably 3.25 ppm / °C or more, and particularly preferably 3.30 ppm / °C or more. 100 / 200 is 3.70 ppm / °C or less, preferably 3.60 ppm / °C or less, more preferably 3.55 ppm / °C or less, and particularly preferably 3.50 ppm / °C or less. 100 / 200 When the thermal expansion coefficient is within the above range, the difference between the thermal expansion coefficient and that of the silicon substrate can be reduced.
[0060] Here, the average thermal expansion coefficient α at 100°C to 200°C 100 / 200 It is an average thermal expansion coefficient in the temperature range of 100°C to 200°C measured by the method specified in JIS R3102 (1995).
[0061] The Young's modulus of the glass substrate of the present invention is below 76.0GPa, preferably below 75.5GPa, more preferably below 75.0GPa, and particularly preferably below 74.0GPa. In addition, the lower limit is not particularly limited, typically more than 60GPa. It can also be more than 65GPa, or more than 70GPa. If the Young's modulus is below 76.0GPa, the grinding rate and the grinding rate can be improved by reducing the toughness of the glass substrate. In addition, the damage caused by contact with the silicon substrate, the peripheral components, etc. can be suppressed. If the Young's modulus is more than 60GPa, the self-weight deflection when the glass substrate is carried can be reduced.
[0062] The density of the glass substrate of the present invention is 2.42 g / cm 3 Above, preferably 2.43 g / cm 3 More preferably, 2.44 g / cm 3 More preferably, 2.45 g / cm 3 In addition, it is preferably 2.55 g / cm 3 Below, more preferably 2.54 g / cm 3 Below, more preferably 2.53 g / cm 3 When the density is within the above range, the brittleness of the glass substrate can be increased, and the grinding rate and polishing rate can be improved.
[0063] For the glass substrate of the present invention, the average thermal expansion coefficient α at 200°C to 300°C is 200 / 300 Divide by the average thermal expansion coefficient α between 50℃ and 100℃ 50 / 100 The obtained value α 200 / 300 / α 50 / 100 It is preferably 1.15 or more, more preferably 1.16 or more, further preferably 1.17 or more, and particularly preferably 1.18 or more.
[0064] In addition, α 200 / 300 / α 50 / 100 It is preferably 1.35 or less, more preferably 1.30 or less, further preferably 1.28 or less, and particularly preferably less than 1.20. 200 / 300 / α 50 / 100 The value may be 1.15 or more and less than 1.20, 1.16 or more and less than 1.20, or 1.18 or more and less than 1.20.
[0065] If α 200 / 300 / α 50 / 100 In the above range, the difference in thermal expansion coefficient with the silicon substrate can be reduced. In particular, the difference in thermal expansion coefficient with the silicon substrate can be reduced in a wide temperature range from room temperature to 300°C. Here, the average thermal expansion coefficient α at 200°C to 300°C is 200 / 300 It is an average thermal expansion coefficient in the temperature range of 200°C to 300°C measured by the method specified in JIS R3102 (1995).
[0066] For the glass substrate of the present invention, the average thermal expansion coefficient α from 200°C to 300°C is 200 / 300 Subtract the average thermal expansion coefficient α from 50℃ to 100℃ 50 / 100 The obtained value α 200 / 300 -α 50 / 100 It is preferably 0.30 or more, more preferably 0.35 or more, and even more preferably 0.40 or more. 200 / 300 -α 50 / 100 It is preferably 1.20 or less, more preferably 1.00 or less, and still more preferably 0.90 or less. 200 / 300 -α 50 / 100 When the temperature is within the above range, the difference in thermal expansion coefficient with the silicon substrate can be reduced. In particular, the difference in thermal expansion coefficient with the silicon substrate can be reduced in a wide temperature range from room temperature to 300°C.
[0067] For the glass substrate of the present invention, the average thermal expansion coefficient α at 200°C to 300°C is 200 / 300 It is preferably 3.45 ppm / °C to 3.95 ppm / °C. 200 / 300 It is more preferably 3.50 ppm / °C or more, further preferably 3.55 ppm / °C or more, particularly preferably 3.60 ppm / °C or more, and most preferably 3.62 ppm / °C or more. 200 / 300 It is more preferably 3.85 ppm / °C or less, further preferably 3.75 ppm / °C or less, particularly preferably 3.73 ppm / °C or less, and most preferably 3.71 ppm / °C or less.
[0068] For the glass substrate of the present invention, the average thermal expansion coefficient α at 50°C to 100°C is 50 / 100 It is preferably 2.70 ppm / °C to 3.20 ppm / °C. 50 / 100 It is more preferably 2.80 ppm / °C or more, further preferably 2.90 ppm / °C or more, particularly preferably 2.91 ppm / °C or more, and most preferably 2.92 ppm / °C or more. 50 / 100 It is more preferably 3.15 ppm / °C or less, further preferably 3.10 ppm / °C or less, particularly preferably 3.05 ppm / °C or less, and most preferably 3.01 ppm / °C or less.
[0069] For the glass substrate of the present invention, the glass transition point (also referred to as Tg) is preferably 680°C or higher, more preferably 685°C or higher, and further preferably 690°C or higher. If Tg is 680°C or higher, the dimensional change of the glass substrate can be suppressed to be small during the heat treatment process. In addition, Tg is preferably 800°C or lower, more preferably 790°C or lower, and most preferably 780°C or lower. If Tg is 800°C or lower, the temperature of the molding device can be reduced, and the life of the molding device can be extended.
[0070] For the glass substrate of the present invention, the viscosity becomes 10 2 The temperature of d·Pa·s (also referred to as T2) is preferably 1700°C or less, more preferably 1680°C or less, and still more preferably 1660°C or less. If T2 is 1700°C or less, the viscosity of the glass will not become too high when it is melted, and the meltability will be good. It should be noted that, considering the ease of ensuring other physical properties, T2 is preferably 1580°C or more.
[0071] For the glass substrate of the present invention, the viscosity becomes 10 4 The temperature of d·Pa·s (also referred to as T4) is preferably 1350°C or less, more preferably 1330°C or less, and further preferably 1310°C or less. If T4 is 1350°C or less, the glass can be easily molded. In addition, T4 is preferably 1200°C or more, more preferably 1250°C or more, and further preferably 1270°C or more. If T4 is 1200°C or more, the glass is less likely to lose clarity in the temperature range during molding, and productivity is improved.
[0072] The devitrification temperature of the glass substrate of the present invention is preferably 1350° C. or less, more preferably 1330° C. or less, and further preferably 1310° C. or less. The devitrification temperature of the glass is the average value of the highest temperature at which crystals are precipitated on the surface and inside of the glass and the lowest temperature at which no crystals are precipitated, when crushed glass particles are placed in a platinum dish and heat treated for 17 hours in an electric furnace controlled at a constant temperature, and observed under an optical microscope after the heat treatment.
[0073] The devitrification viscosity (η) of the glass substrate of the present invention TL ) is preferably 10 3.8 d·Pa·s or more, more preferably 10 3.9 d·Pa·s or more, more preferably 10 4.0 d·Pa·s or more. If the devitrification viscosity is 10 3.8 d·Pa·s or more, molding can be performed stably.
[0074] After the glass substrate of the present invention is bonded to the silicon substrate, it is sometimes directly incorporated as a part of the device. For example, the glass substrate is incorporated into the device as a cover glass. In such a case, in order to miniaturize the device, it is preferred to thin the glass substrate. Therefore, the glass substrate of one embodiment of the present invention is preferably a glass substrate with a high thinning rate. As an indicator of the thinning rate of the glass substrate, the HF weight reduction can be used.
[0075] Here, the HF weight loss is the weight loss per unit area and per unit time when the glass substrate is immersed in a 5 mass % hydrofluoric acid aqueous solution at 25°C [(mg / cm 2 The weight loss of the glass substrate of the present invention relative to the hydrofluoric acid aqueous solution (HF) (hereinafter also referred to as HF weight loss) is preferably 0.07 (mg / cm 2 ) / min or more, more preferably 0.09 (mg / cm 2 ) / min or more, more preferably 0.11 (mg / cm 2 ) / min or more. In addition, it is preferably 0.20 (mg / cm 2 ) / min or less, more preferably 0.18 (mg / cm 2 ) / min or less, more preferably 0.16 (mg / cm 2 ) / minute or less.
[0076] If the HF weight loss is 0.07 (mg / cm 2 ) / min or more, the productivity of the thinning process becomes good and is preferred. If the HF weight loss is 0.20 (mg / cm 2 ) / minute or less, since it is possible to prevent the etching depth that may occur in the glass substrate during the thinning process from becoming uneven and damaging the smoothness of the glass substrate surface, and so it is preferred.
[0077] In addition, the glass substrate of the present invention can be used as a cover glass of a display device for projection purposes, such as LCOS (Liquid Crystal On Silicon). In such a case, if the photoelastic constant of the glass substrate is high, the glass substrate has birefringence due to the stress generated during the packaging process of the device and when the device is used. As a result, the color of the light incident on the device may change, resulting in poor image quality such as color unevenness.
[0078] In order to prevent such poor image quality, the photoelastic constant of the glass substrate of the present invention is preferably 31.0 nm / (MPa·cm) or less, more preferably 30.5 nm / (MPa·cm) or less, further preferably 30.0 nm / (MPa·cm) or less, and particularly preferably 29.5 nm / (MPa·cm) or less.
[0079] The Vickers hardness of the glass substrate of the present invention is preferably 600 or less, more preferably 590 or less, and further preferably 580 or less. The grinding rate can be improved by a Vickers hardness of 600 or less. In addition, the Vickers hardness is preferably 450 or more, more preferably 460 or more, and further preferably 470 or more. The fragility of the glass substrate can be reduced by a Vickers hardness of 450 or more.
[0080] The wear degree of the glass substrate of the present invention is preferably 55 or more, more preferably 56 or more, and further preferably 57 or more. If the wear degree is 55 or more, the grinding rate of the glass substrate can be improved. In addition, the wear degree is preferably 100 or less, more preferably 95 or less, and further preferably 90 or less. If the wear degree is 100 or less, damage caused by contact with a silicon substrate, peripheral components, etc. can be suppressed.
[0081] The thickness of the glass substrate of the present invention is preferably 1.0 mm or less, more preferably 0.8 mm or less, further preferably 0.7 mm or less, and particularly preferably 0.5 mm or less. When the thickness is 1.0 mm or less, the image sensor can be made small.
[0082] In addition, the thickness is preferably 0.1 mm or more, more preferably 0.2 mm or more, and further preferably 0.3 mm or more. If the thickness is 0.1 mm or more, the damage caused by contact with the silicon substrate, peripheral components, etc. can be suppressed. In addition, the self-weight deflection of the glass substrate can be suppressed.
[0083] The area of at least one main surface of the glass substrate of the present invention is preferably 0.03 m 2 More preferably 0.04 m 2 More preferably, 0.05 m 2 If the area is 0.03m 2As described above, a silicon substrate having a large area can be used, and a plurality of image sensors can be manufactured from one multilayer substrate.
[0084] For the glass substrate of the present invention, the density of defects contained in the glass substrate is 1 / cm 2 Below. The defects contained in the glass substrate refer to bubbles, damage, metal foreign matter such as platinum, and unmelted raw materials existing on the surface and inside of the glass substrate, and the size is 0.5μm to 1mm. If the defect is larger than 1mm, it can be easily identified by visual inspection, and the defective substrate can be easily excluded. If the defect is less than 0.5μm, the defect is small enough, so even when it is used as a cover glass for image sensors and LCOS, there is little concern about affecting the characteristics of the device.
[0085] In the conventional semiconductor assembly process, the assembly process is performed after the glass substrate is cut. Therefore, when a glass substrate has defects, the defective substrate can be removed at the beginning of the assembly process. On the other hand, in wafer-level packaging, the single-piece stacked substrate is formed at the end of the assembly process. Therefore, when a glass substrate has defects, the operation of removing the defective glass substrate is performed at the end of the assembly process. Thus, in wafer-level packaging, the cost increase becomes larger when the defect density of the glass substrate increases, and therefore, high-quality defect management is required. The defect density is more preferably 0.1 / cm 2 Below, more preferably 0.01 pieces / cm 2 the following.
[0086] The shape of the glass substrate of the present invention is not particularly limited, and for example, a circle, an ellipse and a rectangle can be cited. In order to match the shape of the bonded silicon substrate, a notch can be provided at the end of the glass substrate, and when the glass substrate is circular, a part of the periphery of the glass substrate can be a straight line.
[0087] For the glass substrate according to one embodiment of the present invention, the virtual viscosity is preferably 10 11.0 d·Pa·s~10 14.1 d·Pa·s. In order to make the virtual viscosity of the glass substrate 10 11.0 d·Pa·s~10 14.1 d·Pa·s, the cooling rate of the glass substrate after molding needs to be equivalent to 1°C / min to 1200°C / min. 11.0 d·Pa·s~10 14.1 d·Pa·s, the average thermal expansion coefficient of the glass substrate is close to the average thermal expansion coefficient of the silicon substrate, and the residual strain generated in the silicon substrate during the heat treatment process of bonding the silicon substrate and the glass substrate is small. The virtual viscosity of the glass substrate is preferably 10 12.1 d·Pa·s~10 13.1d·Pa·s (equivalent to a cooling rate of 10°C / min to 100°C / min).
[0088] The virtual viscosity (η) of glass can be calculated by the following formula [GW Scherer, Relaxation in Glass and Composites, Wiley, New York (1986), p. 159].
[0089] log 10 η=12.3-log 10 |q|
[0090] Here, the unit of η is d·Pa·s, and q is the assumed cooling rate, and the unit is °C / s.
[0091] It is assumed that the cooling rate q can be obtained from the glass substrate by the following method. Cut out a plurality of glass plate pieces from a glass substrate with a thickness of less than 1 mm. For example, cut out a 1 cm square piece as a glass plate piece. Heat treat and cool the cut glass plate pieces at various cooling rates V, and measure the physical properties of each glass plate piece. The cooling start temperature is preferably a sufficiently high temperature that is not affected by the cooling rate. Typically, it is preferably around Tg+50°C to +150°C.
[0092] The physical property values to be measured are not particularly limited, but density and physical properties closely related to density (such as refractive index) are preferred. The x-axis is the cooling rate (log 10 V), the y-axis takes the physical property values of the glass sheets subjected to the heat treatment, and a calibration curve A is prepared. By using the prepared calibration curve A, the assumed cooling rate q of the glass substrate is obtained from the physical property values of the glass sheets not subjected to the heat treatment.
[0093] For the glass substrate of the present invention, the value represented by the following formula (1) is preferably 3.10 or more, more preferably 3.20 or more, further preferably 3.25 or more, and particularly preferably 3.30 or more. In addition, the value represented by the following formula (1) is preferably 3.70 or less, more preferably 3.60 or less, further preferably 3.55 or less, and particularly preferably 3.50 or less. When the value represented by the formula (1) is within the above range, α 100 / 200 By making it a desired value, the difference in thermal expansion coefficient with the silicon substrate can be reduced.
[0094] Formula (1): 0.0181×(SiO2 content)+0.0004×(Al2O3 content)+0.0387×(B2O3 content)+0.0913×(MgO content)+0.1621×(CaO content)+0.1900×(SrO content)+0.2180×(BaO content)+0.0424×(ZnO content)+0.0391×(12.3+log 10 60-log 10 η)
[0095] For the glass substrate of the present invention, the value shown in the following formula (2) is preferably 2.42 or more, more preferably 2.43 or more, further preferably 2.44 or more, and particularly preferably 2.45 or more. In addition, the value shown in the following formula (2) is preferably 2.55 or less, more preferably 2.54 or less, and further preferably 2.53 or less.
[0096] When the value represented by the following formula (2) is within the above range, a process margin can be ensured, and the density and brittleness of the glass substrate can be set to desired values, thereby improving the grinding rate and the polishing rate.
[0097] Formula (2): 0.0218×(SiO2 content)+0.0302×(Al2O3 content)+0.0181×(B2O3 content)+0.0330×(MgO content)+0.0351×(CaO content)+0.0488×(SrO content)+0.0634×(BaO content)+0.0419×(ZnO content)
[0098] For the glass plate of the present invention, the value shown in the following formula (3) is preferably 76.0 or less, more preferably 75.5 or less, further preferably 75.0 or less, and particularly preferably 74.0 or less. By setting the value shown in the following formula (3) to be 76.0 or less, the process margin can be ensured, and the grinding rate and polishing rate can be improved by reducing the toughness of the glass substrate. In addition, damage caused by contact with the silicon substrate, peripheral components, etc. can be suppressed.
[0099] Formula (3): 0.677×(SiO2 content)+1.598×(Al2O3 content)-0.220×(B2O3 content)+1.466×(MgO content)+1.135×(CaO content)+0.667×(SrO content)+0.298×(BaO content)+1.027×(ZnO content)
[0100] For the glass substrate of the present invention, the value represented by the following formula (4) is preferably 1.15 or more, more preferably 1.16 or more, further preferably 1.17 or more, and particularly preferably 1.18 or more. In addition, the value represented by the following formula (4) is preferably 1.35 or less, more preferably 1.30 or less, further preferably 1.28 or less, and particularly preferably less than 1.20.
[0101] The value represented by the following formula (4) may be 1.15 or more and less than 1.20, 1.16 or more and less than 1.20, or 1.18 or more and less than 1.20. The value represented by the following formula (4) is within the above range, α 200 / 300 / α 50 / 100 By making it a desired value, the difference in thermal expansion coefficient with the silicon substrate can be reduced.
[0102] Formula (4): 0.0111×(SiO2 content)+0.0250×(Al2O3 content)+0.0078×(B2O3 content)+0.0144×(MgO content)+0.0053×(CaO content)+0.0052×(SrO content)+0.0013×(BaO content)+0.0121×(ZnO content)-0.0041×(12.3+log 10 60-log 10 η)
[0103] For the glass substrate of the present invention, the value represented by the following formula (5) is preferably 0.30 or more, more preferably 0.35 or more, and further preferably 0.40 or more. In addition, the value represented by the following formula (4) is preferably 1.20 or less, more preferably 1.00 or less, and further preferably 0.90 or less. When the value represented by the following formula (4) is within the above range, α 200 / 300 -α 50 / 100 By making it a desired value, the difference in thermal expansion coefficient with the silicon substrate can be reduced.
[0104] Formula (5): 0.0368×(Al2O3 content)-0.0054×(B2O3 content)+0.0244×(MgO content)+0.0143×(CaO content)+0.0182×(SrO content)+0.0097×(BaO content)+0.097×(ZnO content)-0.0032×(12.3+log 10 60-log 10 η)
[0105] For the glass substrate of the present invention, it is preferred that the value represented by the above formula (1) is 3.10 to 3.70, the value represented by the above formula (2) is 2.42 or more, the value represented by the above formula (3) is 76.0 or less, and it is further preferred that the value represented by the above formula (4) is 1.15 to 1.35, and the value represented by the above formula (5) is 0.30 to 1.20.
[0106] In addition, the α-ray emission of the glass substrate according to one embodiment of the present invention is preferably 0.5 C / cm 2 h or less, more preferably 0.3C / cm 2 h or less, particularly preferably 0.1 C / cm 2 h or less, and most preferably 0.05C / cm 2 ·h or less. It should be noted that the unit C means the count number.
[0107] For example, a glass substrate according to an embodiment of the present invention is applied to a cover glass of an element such as an image sensor. At this time, if α rays generated by the glass substrate are incident on an element such as an image sensor, hole-electron pairs are induced by the energy of the α rays, which may cause soft errors such as bright spots and white spots to appear instantly in the image. Therefore, by using a glass substrate with a small α-ray emission, such an undesirable situation can be easily prevented. It should be noted that if a high-purity raw material with a small content of radioactive isotopes and a small α-ray emission is used as a raw material for the glass substrate, the α-ray emission can be reduced. In addition, in the melting and clarification process of the glass, if the radioactive isotope is not mixed into the molten glass from the furnace material of the glass manufacturing equipment, the α-ray emission can be effectively reduced. In addition, the "α-ray emission" can be measured using an airflow proportional counter tube measuring device or the like.
[0108] The laminated substrate of the present invention is formed by laminating the above-mentioned glass substrate and silicon substrate. The difference in thermal expansion coefficient between the silicon substrate and the glass substrate is small, so the residual strain generated in the silicon substrate in the heat treatment process of laminating the silicon substrate and the glass substrate is small. In addition, the laminated substrate is obtained by laminating the glass substrate and the silicon substrate with a resin sandwiched therebetween.
[0109] At this time, the thickness of the resin, the thermal expansion coefficient of the resin, the heat treatment temperature during bonding, etc. may affect the warping of the entire laminated substrate. The laminated substrate of the present invention can reduce the warping of the entire laminated substrate by controlling the thermal expansion coefficient, as in the glass substrate of one embodiment of the present invention described above, so that the process margins such as the thickness of the resin, the thermal expansion coefficient of the resin, the heat treatment temperature during bonding, etc. can be expanded. The laminated substrate of the present invention can apply the glass substrate of the present invention described above.
[0110] Next, the manufacturing method of the glass substrate of the present invention is described. When manufacturing the glass substrate of the present invention, the following steps are performed: a melting step of heating glass raw materials to obtain molten glass; a clarification step of removing bubbles from the molten glass; a forming step of forming the molten glass into a plate to obtain a glass ribbon; and a slow cooling step of slowly cooling the glass ribbon to room temperature.
[0111] In the melting step, raw materials are prepared so as to have the composition of the obtained glass plate, and the raw materials are continuously charged into a melting furnace and heated preferably to about 1450° C. to 1650° C. to obtain molten glass.
[0112] Raw materials may also be halides such as oxides, carbonates, nitrates, hydroxides, and chlorides. When there is a step in which molten glass contacts platinum during the melting and clarification process, sometimes tiny platinum particles are dissolved in the molten glass and mixed into the obtained glass plate as foreign matter, but the use of a nitrate raw material has the effect of preventing the dissolution of the platinum foreign matter.
[0113] As nitrates, strontium nitrate, barium nitrate, magnesium nitrate, calcium nitrate, etc. can be used. Strontium nitrate is more preferably used. The particle size of the raw material can be appropriately used, ranging from a large particle size of several hundred microns to the extent that no molten residue is generated, to a small particle size of several microns to the extent that the raw material does not scatter during transportation and does not agglomerate in the form of secondary particles. Granulated materials can also be used. In order to prevent the scattering of the raw materials, the water content of the raw materials can be appropriately adjusted. The redox degree of β-OH and Fe or the redox balance (redox) [Fe 2+ / (Fe 2+ +Fe 3+ )] and other melting conditions.
[0114] Next, the clarification step is a step of removing bubbles from the molten glass obtained in the above-mentioned melting step. As the clarification step, a degassing method based on reduced pressure can be applied. In addition, the glass substrate in the present invention can use SO3 and SnO2 as clarifiers. As the SO3 source, it is preferred to select at least one sulfate of an element from Al, Mg, Ca, Sr and Ba, and more preferably an alkaline earth metal sulfate, among which CaSO4·2H2O, SrSO4 and BaSO4 are particularly preferred because of their significant effect of increasing bubbles.
[0115] As a clarifier in the degassing method based on reduced pressure, halogens such as Cl or F are preferably used. As a Cl source, a chloride of at least one element selected from Al, Mg, Ca, Sr and Ba is preferred, and a chloride of an alkaline earth metal is more preferred. Among them, SrCl2·6H2O and BaCl2·2H2O have a significant effect of increasing bubbles and low deliquescent properties, so they are particularly preferred. As a F source, a fluoride of at least one element selected from Al, Mg, Ca, Sr and Ba is preferred, and a fluoride of an alkaline earth metal is more preferred. Among them, CaF2 has a significant effect of increasing the solubility of glass raw materials and is more preferred.
[0116] Next, the forming step is a step of forming the molten glass from which bubbles have been removed in the clarification step into a plate-like shape to obtain a glass ribbon. As the forming step, a float process is used in which the molten glass is poured onto a molten metal to form a plate-like shape to obtain a glass ribbon.
[0117] Next, the slow cooling step is a step of slowly cooling the glass ribbon obtained in the above-mentioned forming step to room temperature. 13 d·Pa·s Temperature until the viscosity becomes 10 14.5 The glass ribbon was slowly cooled to a room temperature state so that the average cooling rate of the temperature in d·Pa·s was R. The slowly cooled glass ribbon was cut to obtain a glass substrate.
[0118] In the method for manufacturing a glass substrate of the present invention, the composition of the obtained alkali-free glass substrate is, in terms of molar percentage based on oxides, 11.0% or more of Al2O3, 8.0% or more of B2O3, and 1% or more of SrO, and the composition of the obtained glass substrate is 10% of the viscosity of the glass ribbon in the slow cooling step. 13 When the temperature of d·Pa·s reaches 10 14.5 The average cooling rate R (unit: °C / min) of the temperature of d·Pa·s satisfies the following conditions (1) to (3). By satisfying conditions (1) to (3), it is possible to manufacture a glass substrate that can improve the grinding / polishing rate and reduce the residual strain generated in the silicon substrate during the heat treatment process.
[0119] Condition (1): 0.0181×(SiO2 content)+0.0004×(Al2O3 content)+0.0387×(B2O3 content)+0.0913×(MgO content)+0.1621×(CaO content)+0.1900×(SrO content)+0.2180×(BaO content)+0.0424×(ZnO content)+0.0391×log 10 R is 3.10~3.70
[0120] Condition (2): 0.0218×(SiO2 content)+0.0302×(Al2O3 content)+0.0181×(B2O3 content)+0.0330×(MgO content)+0.0351×(CaO content)+0.0488×(SrO content)+0.0634×(BaO content)+0.0419×(ZnO content) is 2.42 or more
[0121] Condition (3): 0.677×(SiO2 content)+1.598×(Al2O3 content)-0.220×(B2O3 content)+1.466×(MgO content)+1.135×(CaO content)+0.667×(SrO content)+0.298×(BaO content)+1.027×(ZnO content) is less than 76.0
[0122] In the method for manufacturing a glass substrate of the present invention, it is preferred that the composition of the obtained glass substrate further satisfies the following condition (4). By satisfying conditions (4) and (5), residual strain generated in the silicon substrate during the heat treatment process can be reduced.
[0123] Condition (4)
[0124] 0.0111×(SiO2 content)+0.0250×(Al2O3 content)+0.0078×(B2O3 content)+0.0144×(MgO content)+0.0053×(CaO content)+0.0052×(SrO content)+0.0013×(BaO content)+0.0121×(ZnO content)-0.0041×log 10 R is 1.15~1.35
[0125] Condition (5): 0.0368×(Al2O3 content)-0.0054×(B2O3 content)+0.0244×(MgO content)+0.0143×(CaO content)+0.0182×(SrO content)+0.0097×(BaO content)+0.097×(ZnO content)-0.0032×log 10 R is 0.30 to 1.20. The value shown in the above condition (1) is more preferably 3.20 or more, further preferably 3.25 or more, and particularly preferably 3.30 or more. In addition, the value shown in the above condition (1) is preferably 3.70 or less, more preferably 3.60 or less, further preferably 3.55 or less, and particularly preferably 3.50 or less. By setting the value shown in the condition (1) to the above range, a glass substrate having a small difference in thermal expansion coefficient from a silicon substrate can be manufactured.
[0126] The value shown in the above condition (2) is more preferably 2.43 or more, further preferably 2.44 or more, and particularly preferably 2.45 or more. In addition, the value shown in the above condition (2) is preferably 2.55 or less, more preferably 2.54 or less, and further preferably 2.53 or less. By setting the value shown in the condition (2) to the above range, a glass substrate with high brittleness and good grindability and abrasiveness can be manufactured.
[0127] The value shown in the above condition (3) is more preferably below 75.5, further preferably below 75.0, and particularly preferably below 74.0. By setting the value shown in the above condition (3) to the above range, by being below 76.0, it is possible to ensure process margin and manufacture a glass substrate with low toughness and good grindability and abrasiveness.
[0128] The value shown in the above condition (4) is more preferably greater than 1.16, further preferably greater than 1.17, and particularly preferably greater than 1.18. In addition, the value shown in the above condition (4) is preferably less than 1.30, further preferably less than 1.28, and particularly preferably less than 1.20. The value shown in the condition (4) can be greater than 1.15 and less than 1.20, or greater than 1.16 and less than 1.20, or greater than 1.18 and less than 1.20. By setting the value shown in the above condition (4) to the above range, a glass substrate having a small difference in thermal expansion coefficient with a silicon substrate can be manufactured.
[0129] The value shown in the above condition (5) is more preferably 0.35 or more, and further preferably 0.40 or more. In addition, the value shown in the above condition (4) is preferably 1.20 or less, more preferably 1.00 or less, and further preferably 0.90 or less. When the value shown in the above condition (4) is within the above range, a glass substrate having a small difference in thermal expansion coefficient from a silicon substrate can be manufactured.
[0130] The present invention is not limited to the above-described embodiment, and modifications and improvements within the scope that can achieve the object of the present invention are included in the present invention.
[0131] For example, when manufacturing the glass substrate of the present invention, in the forming step, the molten glass may be formed into a plate shape by applying a melting method, a press forming method, or the like.
[0132] In addition, a platinum crucible may be used when manufacturing the glass substrate of the present invention. When a platinum crucible is used, the raw materials are prepared in a melting step in a manner to form the composition of the obtained glass substrate, and the platinum crucible containing the raw materials is placed in an electric furnace and heated to preferably about 1450° C. to 1650° C. A platinum stirrer is inserted and stirred for 1 to 3 hours to obtain molten glass.
[0133] The forming step flows the molten glass into a carbon plate shape, for example, and forms a plate shape. The slow cooling step slowly cools the plate-shaped glass to room temperature, and after cutting, a glass substrate is obtained. In addition, the cut glass substrate can be heated to, for example, about Tg+50°C, and then slowly cooled to room temperature at a predetermined cooling rate. In this way, the virtual viscosity η can be adjusted.
[0134] Example
[0135] Hereinafter, the present invention will be specifically described with reference to Examples, but the present invention is not limited to these Examples.
[0136] Various glass raw materials such as quartz sand are prepared in such a way as to obtain the glass composition (target composition) shown in Tables 1 to 6. With respect to 100% of the raw materials of the prepared target composition, 0.1% to 1% sulfate, 0.16% F, and 1% Cl are added in terms of mass percentage based on oxides in terms of SO3 conversion. The raw materials are placed in a platinum crucible and melted by heating at a temperature of 1550°C to 1650°C in an electric furnace for 3 hours to prepare molten glass. During melting, a platinum stirrer is inserted into the platinum crucible and stirred for 1 hour to homogenize the glass. The molten glass is poured onto a carbon plate and formed into a plate shape. The plate-shaped glass is then placed in an electric furnace at a temperature of about Tg+50°C, and the electric furnace is cooled at a cooling rate of R (°C / min) until the glass reaches room temperature.
[0137] The virtual viscosity log of the obtained glass was evaluated 10 η (unit: dPa·sec), the value obtained by the following equations (1) to (5), the average thermal expansion coefficient (unit: ppm / °C), the density (unit: g / cm 3 ), Young's modulus (unit: GPa), Vickers hardness, wear resistance, glass transition point Tg (unit: ℃), T2 (unit: ℃), T4 (unit: ℃), devitrification temperature (unit: ℃), devitrification viscosity log 10 η TL (unit: dPa·sec), HF weight loss [unit: (mg / cm 2 ) / min], photoelastic constant [unit: nm / (MPa·cm)]. The results are shown in Tables 1 to 6.
[0138] Formula (1): 0.0181×(SiO2 content)+0.0004×(Al2O3 content)+0.0387×(B2O3 content)+0.0913×(MgO content)+0.1621×(CaO content)+0.1900×(SrO content)+0.2180×(BaO content)+0.0424×(ZnO content)+0.0391×(12.3+log 10 60-log10 η)
[0139] Formula (2): 0.0218×(SiO2 content)+0.0302×(Al2O3 content)+0.0181×(B2O3 content)+0.0330×(MgO content)+0.0351×(CaO content)+0.0488×(SrO content)+0.0634×(BaO content)+0.0419×(ZnO content)
[0140] Formula (3): 0.677×(SiO2 content)+1.598×(Al2O3 content)-0.220×(B2O3 content)+1.466×(MgO content)+1.135×(CaO content)+0.667×(SrO content)+0.298×(BaO content)+1.027×(ZnO content)
[0141] Formula (4): 0.0111×(SiO2 content)+0.0250×(Al2O3 content)+0.0078×(B2O3 content)+0.0144×(MgO content)+0.0053×(CaO content)+0.0052×(SrO content)+0.0013×(BaO content)+0.0121×(ZnO content)-0.0041×(12.3+log 10 60-log 10 η)
[0142] Formula (5): 0.0368×(Al2O3 content)-0.0054×(B2O3 content)+0.0244×(MgO content)+0.0143×(CaO content)+0.0182×(SrO content)+0.0097×(BaO content)+0.097×(ZnO content)-0.0032×(12.3+log 10 60-log 10 η).
[0143] It should be noted that the values in parentheses in the table are obtained by calculation. The residual Fe2O3 in the glass is 50 ppm to 200 ppm by mass parts per million based on oxides, and the residual SO3 is 10 ppm to 100 ppm by mass parts per million based on oxides. The following shows the measurement methods of the various physical properties.
[0144] (Virtual viscosity)
[0145] It was calculated using the above-mentioned formula [GW Scherer, Relaxation in Glass and Composites, Wiley, New York (1986), p. 159].
[0146] (Average thermal expansion coefficient)
[0147] The measurement was carried out using a differential thermal dilatometer (TMA) according to the method specified in JIS R3102 (1995). 50 / 100 The measuring temperature range is 50℃~100℃, α 100 / 200 100℃~200℃ and α 200 / 300 It is 200℃~300℃.
[0148] (Average thermal expansion coefficient of silicon substrate)
[0149] The average thermal expansion coefficient of the silicon substrate (manufactured by Shin-Etsu Chemical Co., Ltd.) is shown in Table 7. Si50 / 100 2.94ppm / ℃, α Si100 / 200 3.37ppm / ℃, α Si200 / 300 3.69ppm / ℃, α Si200 / 300 / α Si50 / 100 is 1.25, α Si200 / 300 -α Si50 / 100 The average thermal expansion coefficient of the silicon substrate is typically the value shown in Table 7.
[0150] (density)
[0151] The measurement was performed by the Archimedean method on a glass block of about 20 g containing no bubbles.
[0152] (Young's modulus)
[0153] The ultrasonic pulse method was used to measure glass with a thickness of 0.5 mm to 10 mm.
[0154] (Vickers hardness)
[0155] The Vickers hardness was measured in accordance with the test method specified in JIS-Z-2244 (2009) (ISO6507-1, ISO6507-4, ASTM-E-384), using a Vickers hardness tester (MICRO HARDNESS TESTER HMV-2) manufactured by SHIMADZU, under normal temperature and humidity (at this time, maintained at room temperature 25°C and humidity 60% RH). Each sample was measured at 10 locations, and its average value was taken as the Vickers hardness of the trial production example. In addition, the indentation load of the Vickers indenter was set to 0.98N and 15 seconds of indentation.
[0156] (Wear)
[0157] As an index for the grinding rate, the wear degree was measured using the measurement method described in the Japan Optical Glass Industry Association Standard J10-1994 "Measurement method for the wear degree of optical glass".
[0158] (Glass transition point Tg)
[0159] The measurement was performed using TMA in accordance with the method specified in JIS R3103-3 (2001).
[0160] (T2)
[0161] The viscosity was measured using a rotational viscometer and the measured viscosity was 10 2 Temperature T2 (℃) at d·Pa·s.
[0162] (T4)
[0163] The viscosity was measured using a rotational viscometer and the measured viscosity was 10 4 Temperature T4 (℃) at d·Pa·s.
[0164] (Devitrification temperature)
[0165] The devitrification temperature is the average of the highest temperature at which crystals precipitate on the surface or inside of the glass and the lowest temperature at which no crystals precipitate, after placing crushed glass particles in a platinum dish and heat treating them in an electric furnace controlled at a constant temperature for 17 hours, and observing them under an optical microscope after the heat treatment.
[0166] (Devitrification viscosity)
[0167] The devitrification viscosity of glass (glass viscosity at the devitrification temperature of glass) is obtained by measuring the glass viscosity of molten glass at high temperature (1000°C to 1600°C) using a rotational viscometer, obtaining coefficients of the Fulcher equation from the obtained results, and then obtaining the coefficients using the Fulcher equation.
[0168] (HF weight reduction)
[0169] The HF weight loss is measured as follows. Cut the glass plate obtained as above, mirror-polish both sides to obtain a glass sample of 40 mm square and 1 mm thickness. After cleaning the glass sample, dry it and measure the weight. Next, immerse the glass sample in 5% by mass hydrofluoric acid maintained at 25°C for 20 minutes, clean it, dry it, measure the weight, and calculate the weight loss from before immersion to after immersion. If the test solution is stirred during immersion, the etching rate changes, so stirring is not implemented. Calculate the surface area based on the sample size, divide the weight loss by the surface area, and then divide it by the immersion time, thereby calculating the weight loss per unit area and per unit time (HF weight loss).
[0170] (Photoelastic constant)
[0171] The measurement was carried out by the circular plate compression method ("Measurement of the photoelastic constants of chemically strengthened glass by the circular plate compression method", Yokota Ryosuke, Journal of the Ceramic Industry Association, 87
[10] , 1979, pp.519-522).
[0172] [Table 1]
[0173]
[0174] [Table 2]
[0175]
[0176] [Table 3]
[0177]
[0178] [Table 4]
[0179]
[0180] [Table 5]
[0181]
[0182] [Table 6]
[0183]
[0184] [Table 7] [Table 7]
[0185] Silicon substrate <![CDATA[α Si50 / 100 ]]> 2.94ppm / ℃ <![CDATA[α Si100 / 200 ]]> 3.37ppm / ℃ <![CDATA[α Si200 / 300 ]]> 3.69ppm / ℃ <![CDATA[α si200 / 300 / a Si50 / 100 ]]> 1.25 <![CDATA[α Si200 / 300 -a Si50 / 100 ]]> 0.75ppm / ℃
[0186] [Table 8]
[0187] [Table 8]
[0188] Example 9 Example 10 Example 40 Wear 60 57 51
[0189] [Table 9]
[0190] [Table 9]
[0191] Example 1 Example 14 Example 18 Example 26 Example 29 Wear 60 57 59 58 62
[0192] Examples 1 to 19 and 22 to 29 are examples, Examples 20 and 21 are reference examples, and Examples 30 to 71 are comparative examples. The average thermal expansion coefficient α of the alkali-free glass substrates of Examples 1 to 29 at 100°C to 200°C is 100 / 200 The Young's modulus is 76 GPa or less, and the density is 2.42 g / cm3 As described above, the grinding rate when grinding the glass can be easily improved.
[0193] α of the glass substrates of Examples 30 to 71 100 / 200 , Young's modulus, and density are out of the range of the glass substrate of one embodiment of the present invention. 200 / 300 / α 50 / 100 The range of is out of the preferred range involved in the glass substrate of one embodiment of the present invention. In addition, the composition of the glass substrate obtained by the glass substrates of Examples 30 to 54 and 56 to 71, and the range of any one or more of (1) to (4) are out of the preferred range involved in the glass substrate of one embodiment of the present invention. Therefore, in the heat treatment process of bonding the silicon substrate and the glass substrate, the residual strain generated in the silicon substrate is likely to become large. In addition, in the process of grinding the glass substrate, the grinding rate is likely to become small.
[0194] Table 8 shows the values of the wear degree of Examples 9, 10, and 40. In addition, Table 9 shows the values of the wear degree of Examples 1, 14, 18, 26, and 29. As shown in Tables 8 and 9, the glass substrates of Examples 1, 9, 10, 14, 18, 26, and 29 as examples have high wear degrees, and the glass substrate of Example 40 as a comparative example has low wear degrees. As can be seen from the above, the alkali-free glass substrate according to one embodiment of the present invention can improve the grinding rate.
[0195] In addition, Figure 2 The value obtained by equation (1) and α are shown. 100 / 200 A graph showing the error in the value of . Figure 3 A graph showing the value obtained by equation (2) and the density error is shown. Figure 4 A graph showing the value obtained by the formula (3) and the error in the Young's modulus is shown. Figure 5 The value obtained by equation (4) and α are shown. 200 / 300 / α 50 / 100 A graph showing the error in the value of . Figure 6 The value obtained by equation (5) and α are shown. 200 / 300 -α 50 / 100 The error of the value of is plotted in a graph. Figure 2 to Figure 6 As shown, it can be seen that the values obtained by equations (1) to (5) are correlated with the measured values.
[0196] Although the present invention has been described in detail with reference to a specific mode, it is obvious to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the present invention. It should be noted that this application is based on Japanese patent applications (Japanese patent application 2016-104652) filed on May 25, 2016 and Japanese patent applications (Japanese patent application 2016-154685) filed on August 5, 2016, which are incorporated herein by reference in their entirety. In addition, all references cited herein are incorporated as a whole.
[0197] Industrial Applicability
[0198] The difference in thermal expansion coefficient between the glass substrate of the present invention and the silicon substrate is small, so the generation of residual strain caused by the difference in thermal expansion coefficient can be suppressed in the heat treatment process of bonding with the silicon substrate and the subsequent heat treatment process. Therefore, it is suitable as a glass substrate for image sensors such as MEMS, CMOS, CIS, etc., which are effective in miniaturizing components by wafer-level packaging.
[0199] In addition, it is suitable for use as a cover glass for display devices for projection purposes, such as a cover glass for LCOS. For example, for LCOS and image sensors, after forming an electronic circuit on a silicon substrate, a resin or glass powder is used as an adhesive material to bond the cover glass to the silicon substrate. The glass substrate of the present invention has a small difference in thermal expansion coefficient between the silicon substrate and the cover glass, thereby reducing the stress generated at the bonding interface when the temperature changes during device manufacturing and use. As a result, it can be expected to reduce color unevenness caused by photoelastic deformation and improve long-term reliability.
[0200] Furthermore, the glass substrate of the present invention is suitable as a perforated substrate of a glass interposer (GIP) and a support glass for semiconductor back grinding. In addition, the glass substrate of the present invention can be appropriately used as long as it is used in conjunction with a silicon substrate.
[0201] Explanation of symbols
[0202] 10Silicon substrate
[0203] 20 resin
[0204] 30-layer substrate
[0205] G1 Glass Substrate
Claims
1. An alkali-free glass substrate, comprising, in terms of molar percentage on an oxide basis, 11.0% or more of Al2O3, 8.0% or more of B2O3, 0-5.1% of CaO, and 1% or more of SrO, and having an average thermal expansion coefficient of α at 100°C to 200°C 100 / 200 The temperature is 3.10ppm / ℃~3.70ppm / ℃, the Young's modulus is below 76.0GPa, and the density is 2.42g / cm 3 above.
2. The alkali-free glass substrate according to claim 1, wherein The composition is as follows based on the molar percentage of the oxide: SiO2: 50% to 75%, Al2O3: 11.0% to 16%, B2O3: 9.2% to 16%, MgO: 0% to 10%, CaO: 0% to 4.6%, SrO: 1% to 10%, BaO: 0% to 10%, ZnO: 0% to 10%.
3. The alkali-free glass substrate according to claim 1 or 2, wherein The content of CaO is 0 to 3.0% and SrO is 5.1 to 10% in terms of molar percentage based on oxides.
4. The alkali-free glass substrate according to claim 1 or 2, wherein The total content of MgO and CaO is 1.0% or more in terms of molar percentage based on oxides.
5. The alkali-free glass substrate according to any one of claims 1 to 4, wherein Average thermal expansion coefficient α at 200℃~300℃ 200 / 300 Divide by the average thermal expansion coefficient α between 50℃ and 100℃ 50 / 100 The obtained value α 200 / 300 / α 50 / 100 It is 1.15~1.
35.
6. The alkali-free glass substrate according to any one of claims 1 to 4, wherein Average thermal expansion coefficient α at 200℃~300℃ 200 / 300 Divide by the average thermal expansion coefficient α between 50℃ and 100℃ 50 / 100 The obtained value α 200 / 300 / α 50 / 100 It is 1.15 or more and less than 1.
20.
7. The alkali-free glass substrate according to any one of claims 1 to 6, wherein Average thermal expansion coefficient α from 200℃ to 300℃ 200 / 300 Subtract the average thermal expansion coefficient α from 50℃ to 100℃ 50 / 100 The obtained value α 200 / 300 -α 50 / 100 It is 0.30~1.
20.
8. The alkali-free glass substrate according to any one of claims 1 to 7, wherein The glass transition point is 680°C or higher.
9. The alkali-free glass substrate according to any one of claims 1 to 8, wherein The wear degree is 55 or above. 10 . The alkali-free glass substrate according to claim 1 , wherein Vickers hardness is 600 or less. 11 . The alkali-free glass substrate according to claim 1 , which is used for at least one of a supporting substrate and a cover glass for a semiconductor manufacturing process.
12. The alkali-free glass substrate according to any one of claims 1 to 11, wherein At least one major surface has an area of 0.03 m 2 above.
13. The alkali-free glass substrate according to any one of claims 1 to 12, wherein The thickness is less than 1.0 mm.
14. The alkali-free glass substrate according to any one of claims 1 to 13, wherein The density of defects of 0.5 μm to 1 mm contained in the glass substrate is 1 / cm 2 the following.
15. The alkali-free glass substrate according to any one of claims 1 to 14, wherein The value represented by the following formula (1) is 3.10 to 3.70, Formula (1): 0.0181×(SiO2 content)+0.0004×(Al2O3 content)+0.0387×(B2O3 content)+0.0913×(MgO content)+0.1621×(CaO content)+0.1900×(SrO content)+0.2180×(BaO content)+0.0424×(ZnO content)+0.0391×(12.3+log 10 60-log 10 η) In formula (1), the contents of SiO2, Al2O3, B2O3, MgO, CaO, SrO, BaO and ZnO are expressed as molar percentages based on the oxides contained in the obtained glass, and η is a virtual viscosity with a unit of d·Pa·s.
16. The alkali-free glass substrate according to any one of claims 1 to 15, wherein The value represented by the following formula (2) is 2.42 or more, Formula (2): 0.0218×(SiO2 content)+0.0302×(Al2O3 content)+0.0181×(B2O3 content)+0.0330×(MgO content)+0.0351×(CaO content)+0.0488×(SrO content)+0.0634×(BaO content)+0.0419×(ZnO content) In formula (2), the contents of SiO2, Al2O3, B2O3, MgO, CaO, SrO, BaO and ZnO are expressed as molar percentages based on the oxides contained in the obtained glass.
17. The alkali-free glass substrate according to any one of claims 1 to 16, wherein The value represented by the following formula (3) is 76.0 or less, Formula (3): 0.677×(SiO2 content)+1.598×(Al2O3 content)-0.220×(B2O3 content)+1.466×(MgO content)+1.135×(CaO content)+0.667×(SrO content)+0.298×(BaO content)+1.027×(ZnO content) In formula (3), the contents of SiO2, Al2O3, B2O3, MgO, CaO, SrO, BaO and ZnO are expressed as molar percentages based on the oxides contained in the obtained glass.
18. The alkali-free glass substrate according to any one of claims 1 to 17, wherein The value represented by the following formula (4) is 1.15 to 1.35, Formula (4): 0.0111×(SiO2 content)+0.0250×(Al2O3 content)+0.0078×(B2O3 content)+0.0144×(MgO content)+0.0053×(CaO content)+0.0052×(SrO content)+0.0013×(BaO content)+0.0121×(ZnO content)-0.0041×(12.3+log 10 60-log 10 η).
19. The alkali-free glass substrate according to any one of claims 1 to 18, wherein The value represented by the following formula (5) is 0.30 to 1.20, Formula (5): 0.0368×(Al2O3 content)-0.0054×(B2O3 content)+0.0244×(MgO content)+0.0143×(CaO content)+0.0182×(SrO content)+0.0097×(BaO content)+0.097×(ZnO content)-0.0032×(12.3+log 10 60-log 10 η) In formula (5), the contents of Al2O3, B2O3, MgO, CaO, SrO, BaO and ZnO are expressed as molar percentages based on the oxides contained in the obtained glass.
20. An alkali-free glass substrate, comprising, in terms of molar percentage based on oxides, 11% or more of Al2O3 and 0 to 5.1% of CaO, and having an abrasion resistance of 55 or more, used for at least one of a supporting substrate and a cover glass for a semiconductor manufacturing process. 21 . A laminated substrate comprising the alkali-free glass substrate according to claim 1 and a silicon substrate laminated together.
22. A method for manufacturing an alkali-free glass substrate, comprising the following steps: The melting step is to heat the glass raw materials to obtain molten glass. a clarification step to remove bubbles from the molten glass, a forming step of forming the molten glass into a plate-shaped glass ribbon, and A slow cooling step, slowly cooling the glass ribbon to room temperature; The composition of the obtained glass substrate contains, in terms of molar percentage based on oxides, more than 11.0% of Al2O3, more than 8.0% of B2O3, 0 to 5.1% of CaO, and more than 1% of SrO. The composition of the obtained glass substrate and the viscosity of the glass ribbon in the slow cooling step are 10 13 When the temperature of d·Pa·s reaches 10 14.5 The average cooling rate R of the temperature of d·Pa·s satisfies the following conditions (1) to (3), and the unit of the average cooling rate R is °C / min. Condition (1): 0.0181×(SiO2 content)+0.0004×(Al2O3 content)+0.0387×(B2O3 content)+0.0913×(MgO content)+0.1621×(CaO content)+0.1900×(SrO content)+0.2180×(BaO content)+0.0424×(ZnO content)+0.0391×log 10 R is 3.10~3.70, Condition (2): 0.0218×(SiO2 content)+0.0302×(Al2O3 content)+0.0181×(B2O3 content)+0.0330×(MgO content)+0.0351×(CaO content)+0.0488×(SrO content)+0.0634×(BaO content)+0.0419×(ZnO content) is 2.42 or more, Condition (3): 0.677×(SiO2 content)+1.598×(Al2O3 content)-0.220×(B2O3 content)+1.466×(MgO content)+1.135×(CaO content)+0.667×(SrO content)+0.298×(BaO content)+1.027×(ZnO content) is less than 76.0, In conditions (1) to (3), the contents of SiO2, Al2O3, B2O3, MgO, CaO, SrO, BaO and ZnO are expressed as molar percentages based on the oxides contained in the obtained glass.
23. The method for manufacturing an alkali-free glass substrate according to claim 22, wherein: The composition of the obtained glass substrate further satisfies the following conditions (4) and (5), Condition (4): 0.0111×(SiO2 content)+0.0250×(Al2O3 content)+0.0078×(B2O3 content)+0.0144×(MgO content)+0.0053×(CaO content)+0.0052×(SrO content)+0.0013×(BaO content)+0.0121×(ZnO content)-0.0041×log 10 R is 1.15~1.35, Condition (5): 0.0368×(Al2O3 content)-0.0054×(B2O3 content)+0.0244×(MgO content)+0.0143×(CaO content)+0.0182×(SrO content)+0.0097×(BaO content)+0.097×(ZnO content)-0.0032×log 10 R is 0.30~1.20, In conditions (4) and (5), the contents of Al2O3, B2O3, MgO, CaO, SrO, BaO and ZnO are expressed in molar percentage based on the oxides contained in the obtained glass.
24. The method for producing an alkali-free glass substrate according to claim 22 or 23, wherein: The composition of the obtained glass substrate contains 0 to 3.0% of CaO and 5.1 to 10% of SrO in terms of molar percentage based on oxides.
Citation Information
Patent Citations
Module type distribution system
JP2016104652A
catheter
JP2016154685A